Pendidikan Politik Dalam Mencerdaskan Regenerasi Muda Melalui Sekolah - Fakhrurrazi, Fakhrurrazi (Universitas Malikussaleh, 2013)
Political education is a conscious effort, and aims to create a cadre of qualified nation in political life. Political education is not only true for adults who will become members or officials of political parties, but political education can be applied to school children, because these children are part of a community that has the right and obligation to the children and this is the time political future at stake. Political education in schools is also expected to create a political regeneration, because one political education success lies not in how political parties could produce the countrys leaders, but political success can be seen from the success of creating a political regenarsi through school education. The process of political education through school is a shared responsibility, and therefore directly related to the formal responsibilities stakeholders (school elements) is needed. Political education in schools can be reached in several ways, including through school curricula in particular subjects Citizenship Education, or the means of most concrete is through school student organizations, such as the Inter-School Students Organization (OSIS) and Praja Muda Karana (SCOUT).